Potential Factors Canceling Interannual Cycles of Shoot Production in a Moso Bamboo (Phyllostachys pubescens) Stand - Lin, Chuan-Ya; Miki, Takeshi; Kume, Tomonori (Frontiers in Forests and Global Change, 2022)
Moso bamboo (Phyllostachys pubescens) forests are utilized for food, building materials, and carbon fixation in East Asia. Hence, understanding the factors that influence productivity is important. Long-term records of managed Moso bamboo forests have provided evidence for 2-year cycles of new shoot production. A widely accepted explanatory hypothesis is that the 2-year leaf life span and unequal proportions of newer and older leaves in bamboo stands are the cause of the 2-year shoot production cycle. However, 2-year cycles are not observed in all circumstances. If the 2-year leaf life span causes the biennial production cycle, why are the 2-year cycles of new shoot production not observed in some periods? By constructing an age-structured population growth model that considered the Moso bamboo leaf life span, this study aimed to clarify the possible mechanisms that could suppress the 2-year cycle of new shoot production. The simulation demonstrated that the 2-year cycle may readily disappear because of the contribution of considerable carbohydrates originating from photosynthesis in old leaves and in new leaves of zero-year-old culms, and from belowground carbon storage in roots and rhizomes. The results suggested that the contribution of photosynthesis in old leaves and in new leaves of zero-year-old culms may be overlooked at the population scale, and that belowground carbon storage in Moso bamboo rhizome systems might act as buffer to stabilize the year-to-year variations in new shoot production.